Duvelisib, an oral dual PI3K‐δ, γ inhibitor, shows clinical activity in indolent non‐Hodgkin lymphoma in a phase 1 study. Issue 11 (31st August 2018) - Flinn, Ian W.; Patel, Manish; Oki, Yasuhiro; Horwitz, Steven; Foss, Francine F.; Allen, Kerstin; Douglas, Mark; Stern, Howard; Sweeney, Jennifer; Kharidia, Jahnavi; Kelly, Patrick; Kelly, Virginia M.; et al.
Abstract: Duvelisib (IPI‐145) is an oral dual inhibitor of phosphoinositide‐3‐kinase (PI3K)‐δ and ‐γ in clinical development for the treatment of hematologic malignancies, including indolent non‐Hodgkin lymphoma (iNHL). In a Phase 1, open‐label study to determine the maximum tolerated dose (MTD), pharmacokinetics, pharmacodynamics, clinical activity, and safety of duvelisib monotherapy in patients with advanced hematologic malignancies, duvelisib was administered at eight dose levels (8‐100 mg BID) in a dose‐escalation phase ( n = 31 evaluable patients). Two dose‐limiting toxicities (DLTs), Grade 3 transaminase elevations and Grade 3 rash, occurred at 100 mg BID, and the MTD was determined to be 75 mg BID. Across all doses, 58.1% of iNHL patients had a response (19.4% complete, 35.5% partial, and 3.2% minor); median time to response was 1.84 months and duration of response was 16.9 months. Median progression‐free survival was 14.7 months, and the probability of overall survival at 24 months was 71.7%. Severe (Grade ≥ 3) adverse events included elevated liver enzymes (38.7%), diarrhea (25.8%), and neutropenia (29.0%). Three patients, all in the 75 mg BID cohort, experienced fatal AEs: E. coli sepsis, acute respiratory failure, and fungal pneumonia. No iNHL patients experienced Pneumocystis pneumonia. Duvelisib demonstrated favorable clinical activity and an acceptable safety profile in these high‐risk, heavily pretreated, relapsed/refractory iNHL patients, with 25 mg BID selected for further clinical development.